KOMPETENSI KEPRIBADIAN GURU DI MADRASAH ALIYAH TAHFIZHIL QUR’AN MEDAN - M. Adlin Damanik, Siti Aminatun Suryani (Universitas Islam Negeri Sumatera Utara Medan, 2020)
The purpose of this study was to determine: 1) Personality competence of teachers at Madrasah Aliyah Tahfizhil Qur'an Medan, 2) How to improve teacher personality competence at Madrasah Aliyah Tahfizhil Qur'an Medan, 3) Factors that influence teacher personality at Madrasah Aliyah Tahfizhil Qur 'an Medan. This study uses qualitative research methods, and this research technique uses observation, interview and documentation techniques. The informants in this study were the head of madrasah, administrative staff, teachers. Validity testing of data using triangulation, credibility test (credibility), transferability test (transferability). And can be done with a dependency test (dependility). The results showed that: 1) The personality competence of Madrasah Aliyah Tahfizhil Qur'an teachers greatly affects the performance of a teacher, the ability of this teacher to fulfill his duties as an educator so that it is carried out properly. The personality of a teacher at Madrasah Aliyah Tahfizhil Qur'an Medan determines whether or not an educator is good for his students. 2) How to improve the personality competence of teachers at Madrasah Aliyah Tahfizhil Qur'an Medan, the principal of the school conducts ARD (Digital Report Card Application) training and socializing. 3) The factors that affect the competence of teachers in Madrasah Aliyah Tahfizhil Qur'an Medan are influenced by two factors, namely internal and external factors. Internal factors come from within the teacher himself and external factors come from the outside environment starting from the smallest environment such as family, friends, neighbors and so on.